Wives' Work and Family Income Mobility - Katharine Bradbury; Jane Katz (Federal Reserve Bank of Boston, 2004)
Married women in the United States are increasingly integral to their families' economic wellbeing. With two-earner families becoming the norm, little research investigates the role of wives in family income mobility. How much does a wife's labor market activity matter in her family's ability to gain or hold its place in the income distribution of all families? Are women's contributions to mobility weaker when children are present? Do more-educated wives make bigger contributions than wives with less education? Using the Panel Study of Income Dynamics to observe families at the beginning and end of three 10- year periods spanning the 1970s, 1980s, and 1990s, we find that married-couple families moving up the income distribution saw larger increases in wives' employment, annual work hours, and earnings than downwardly mobile married couples. These data confirm the popular perception that families needed to work more hours to move ahead or hold their own in the income distribution. In upwardly mobile families, wives' work hours increased substantially, while husbands' hours increased only modestly. Wives with children living at home were less likely to work and averaged fewer work hours; however, wives in upwardly mobile families with children increased their work hours more than those in upwardly mobile families without children. Less-educated wives' earnings gains were critically important to their families' advancement. Moreeducated wives also helped their families move up, but their contributions were surpassed by the earnings gains of their husbands.
Keywords: J22; J24; I31; D13; J16; D31; J31; 330; family income; income mobility; income inequality; PSID; working wives; women?s earnings; hours of work; Haushaltseinkommen; Frauenerwerbstätigkeit; Einkommensverteilung; Erwerbsverlauf; Bildungsverhalten; USA